2017
DOI: 10.11591/ijece.v7i6.pp3753-3760
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Harmonic and Interharmonic Contribution of Electric Arc Furnace by Using Periodogram

Abstract: Fast and accurate detection of the harmonic and interharmonic contribution of electric arc furnace (EAF) is crucial in identifying and to mitigate the undesired effects to the system.  In this paper, periodogram, a fast and accurate technique is introduced for the analysis of the contribution. Based on a rule-based classifier and the threshold settings that referred to the IEEE Standard 1159 2009, the analysis of the harmonic and interharmonic contribution of EAF are carried out successfully. Moreover, the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The spectrum of interharmonics for the furnace with a capacity of 100 tons is in the frequency range of 0.01-2.0 Hz; their energy is about 20 % of all mixed spectrum energy [5]. Study [6] showed the presence of a spectrum of interharmonics at frequencies above 200 Hz, as well as a constant component in the current of the arc whose value is correlated with the rated current of the furnace transformer magnetization. A wide range of higher harmonics was reported in [7]; the study results show the existence of individual harmonics of the furnace current with a value of 12 %, and a constant component of 3 %, of the rated current of the furnace.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The spectrum of interharmonics for the furnace with a capacity of 100 tons is in the frequency range of 0.01-2.0 Hz; their energy is about 20 % of all mixed spectrum energy [5]. Study [6] showed the presence of a spectrum of interharmonics at frequencies above 200 Hz, as well as a constant component in the current of the arc whose value is correlated with the rated current of the furnace transformer magnetization. A wide range of higher harmonics was reported in [7]; the study results show the existence of individual harmonics of the furnace current with a value of 12 %, and a constant component of 3 %, of the rated current of the furnace.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…This paper proposes a high accuracy, fast estimation and costs efficient technique to identify and diagnose the type of multiple harmonic sources in the distribution system with single point measurement at the point of common coupling (PCC) by utilizing the machine learning techniques [28,29]. The machine learning such as support vector machine (SVM) and Naïve Bayes are used to classify and diagnose the location and type of harmonic sources.…”
Section: Introductionmentioning
confidence: 99%
“…Harmonic distortion can decrease the accuracy of the electrical meter. Harmonic distortion may also cause excessive dissipation of electrical equipment so as to increase the cost of the bill [9], [10]. Furthermore, harmonic distortion causes electrical equipment not to work on the specified power quality standards causing a decrease in the lifetime of the electrical equipment [11], [12].…”
Section: Introductionmentioning
confidence: 99%